DNA Methylation in Skeletal Muscle Stem Cell Specification, Proliferation, and Differentiation - Rhianna C. Laker; James G. Ryall (Stem Cells International)
An unresolved and critically important question in skeletal muscle biology is how muscle stem cells initiate and regulate the genetic program during muscle development. Epigenetic dynamics are essential for cellular development and organogenesis in early life and it is becoming increasingly clear that epigenetic remodeling may also be responsible for the cellular adaptations that occur in later life. DNA methylation of cytosine bases within CpG dinucleotide pairs is an important epigenetic modification that reduces gene expression when located within a promoter or enhancer region. Recent advances in the field suggest that epigenetic regulation is essential for skeletal muscle stem cell identity and subsequent cell development. This review summarizes what is currently known about how skeletal muscle stem cells regulate the myogenic program through DNA methylation, discusses a novel role for metabolism in this process, and addresses DNA methylation dynamics in adult skeletal muscle in response to physical activity.